Design and application of grid cloud testing service platform - Xiaorong CHANG; Chunguang ZHANG; Sining WANG; Junwei ZHANG; Jiamei WU (Dianxin kexue, 2017)
With the rapid development of big data and cloud computing technology,and successful practice in domestic and foreign enterprises,how to introduce the cloud computing technology,to innovate the traditional test mode,to achieve the conversion of the traditional software testing to the cloud model test mode,become the key to software quality assurance for the enterprise.For cloud platform has strong processing ability,large storage capacity,safety and reliability,moderate distribution capacity,grid cloud testing service platform will meet the advanced,practical,safety and other characteristics,to provide internal and external cloud testing services for enterprises.The application of mobile testing in the cloud platform was enumerated,the availability of the grid cloud testing service platform was verified,the advantages of the platform were analyzed.